Association between carotid atherosclerotic plaque characteristics and white matter hyperintensity in cerebral small vessel disease - Feng, Qiuhao; Wang, Tianle; Zhu, Li (Frontiers in Neurology, 2026)
ObjectiveThis study aimed to investigate the relationship between carotid atherosclerotic plaque characteristics, as assessed by computed tomography angiography (CTA), and white matter hyperintensity (WMH) in patients with carotid atherosclerosis.MethodsA total of 180 patients with carotid atherosclerosis who underwent both carotid CTA and brain MRI were retrospectively enrolled. WMH severity on T2-weighted fluid-attenuated inversion recovery (T2-FLAIR) images was graded using the Fazekas scale, with patients categorized into the none/mild (n = 77) and severe (n = 103) WMH groups. Plaque thickness, length, and stenosis were measured on CTA multiplanar reconstruction (MPR) and curved planar reformation (CPR) images. Plaque calcification types were classified according to Saba’s criteria. Quantitative WMH volumes were automatically segmented into four subregions using an artificial intelligence-assisted platform. Logistic regression and Spearman correlation analyses were performed to evaluate associations between plaque characteristics and WMH burden.ResultsPatients with severe WMH exhibited greater plaque thickness (4.20 vs. 2.80 mm, p < 0.001) and higher stenosis (52.0% vs. 28.0%, p < 0.001). After multivariate adjustment using a fully adjusted model including demographic variables, vascular risk factors, and lipid profile parameters, maximal plaque thickness (OR = 1.669) and stenosis degree (OR = 1.044) remained independent predictors of severe WMH (p < 0.001). Plaque thickness showed the strongest correlations with WMH volumes in the periventricular (r = 0.429) and juxtaventricular (r = 0.383) regions (p < 0.001), whereas plaque length showed no significant associations. Rim sign-positive calcified plaques (type 6) were significantly correlated with total WMH volume (β = 0.359, p = 0.045).ConclusionCarotid plaque thickness and stenosis are independently associated with WMH severity, particularly affecting periventricular regions. These findings suggest that carotid atherosclerosis may contribute to cerebral small vessel disease (CSVD) progression through hemodynamic or embolic mechanisms.